Comparison of 3D Reconstruction Tools for Public Participation in Architectural Heritage Conservation - Li, Qingxiang; Yang, Guidong; Long, Lingege (MAJ - Malaysia Architectural Journal, 2025)
Traditionally, heritage conservation has been chiefly led by government, with an emphasis on protecting well-known architectural treasures. However, a substantial portion of architectural heritage consists of lesser-known and remote architectures, often neglected, inadequately preserved and documented. As depicted in the memorable quote from the movie CoCo, "Death is not the end of life, forgetting is the end of life". This sentiment is also highly suitable to be used in lesser-known architectural heritage. They still exist worldwide, harboring history, culture, art, and narratives amidst the dust of time. But they have been largely forgotten by the world and left in obscurity. Consequently, there is an urgent need to establish a bottom-up approach that actively involves the public in the preservation of lesser-known heritage sites. The process of capturing the 3D geometries and surface textures of architectural heritage represents an easily comprehensible undertaking for the public. Three-dimension (3D) reconstruction method is a good way to document the 3D information of architectural heritage. Numerous 3D reconstruction tools are available, making it imperative to identify one that stands out for its accessibility and user-friendliness, particularly for the public. Hakka Tulou, Zhenchenglou, is selected as a case in this study. 4 tools, including Metashape, Pix4D, DJI Terra, and CU-Recon, are used to reconstruct this heritage building. A survey is conducted to figure out the satisfaction level of the reconstruction outcomes by the four tools. The reconstruction results are compared in four aspects, including clearness, accuracy, integrity, authenticity. This study introduces a new way for public participation in architectural heritage conservation and provides deep insights into the documentation of architectural heritage.